PENGGUNAAN MODEL PEMBELAJARAN QUANTUM TEACHING DALAM MENGEMBANGKAN AKTIVITAS BELAJAR SISWA PADA PEMBELAJARAN IPS - Hernawati, Ade (2016)
This research is motivated by a preliminary study in class VII N SMPN 29 Bandung. In the preliminary study, it is found that the students' learning activity is very low. The low activity of learning, in the research case was addressed by Quantum Teaching Learning model. Seeing the problems to be studied with regard to the learning process, the researchers chose a classroom action research (PTK) models Kemmis and Taggart. The use of Quantum Teaching learning models has become an alternative solution to increase the activity of students in social studies learning. This is because the election of Quantum teaching can be a means to allow the teacher give the material, visualize and connect with the knowledge of what has been owned by the students. In the improvement of student learning activities, the researchers chose five indicators of learning activity as a reference in the research as follows: a) Visual Activities, b) Oral Activities, c) Listening Activities, d) Writing Activities, e) Emotional Activities. Based on those indicators, the research was conducted in class VII N on 13-27 April 2016 with the topic of the future development of Islam in Indonesia, future European nations in Indonesia, and the agency is committed in several cycles. The research results indicate that students experience the development in all of the aforementioned indicators of learning activities from the first cycle to the third cycle. Particularly, the highest learning activity indicators using model Quantum Teaching are the indicator of visual and emotional activity. While the weakest are in the listening activity indicator. ;--- Penelitian ini dilatarbelakangi oleh studi pendahuluan di SMPN 29 Bandung kelas VII N. Studi pendahuluan ditemukan bahwa aktivitas belajar siswa sangat rendah. Rendahnya aktivitas belajar, dalam kasus penelitian dicoba diatasi dengan model Pembelajaran Quantum Teaching. Melihat permasalahan yang akan diteliti berkaitan dengan proses pembelajaran, maka peneliti memilih penelitian tindakan kelas (PTK) model Kemmis dan Taggart. Penggunaan model pembelajaran Quantum Teaching dipilih menjadi alternatif pemecahan masalah untuk meningkatkan aktivitas belajar siswa dalam pembelajaran IPS. Pemilihan ini dikarenakan Quantum teaching dapat menjadi sarana untuk memungkinkan guru memberikan materi, menvisualisasikan dan menghubungkan dengan pengetahuan apa yang telah dimiliki siswa. Dalam peningkatan aktivitas belajar siswa, peneliti memilih 5 indikator aktivitas belajar sebagai acuan dalam penelitian yaitu: a) Aktivitas Visual, b) Aktivitas Lisan, c) Aktivitas Mendengarkan, d) Aktivitas Menulis, e) Aktivitas Emosional. Berdasarkan indikator tersebut, penelitian ini dilaksanakan di kelas VII N pada tanggal 13 April 2016 - 27 April 2016, dengan topik perkembangan masa Islam di Indonesia, masa bangsa eropa di Indonesia, dan badan usaha dilakukan dalam beberapa siklus. Hasil penilitian menunjukkan bahwa siswa mengalami perkembangan dalam seluruh indikator aktivitas belajar dari siklus pertama sampai siklus ketiga. Khususnya, indikator aktivitas belajar menggunakan model pembelajaran Quantum Teaching yang paling tinggi adalah terdapat pada indikator aktivitas visual dan aktivitas emosional. Sedangkan yang paling lemah terdapat pada indikator aktivitas mendengarkan.